2016
DOI: 10.1016/j.jmii.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

VDR and VDBP genes polymorphisms associated with susceptibility to tuberculosis in a Han Taiwanese population

Abstract: The polymorphisms in the VDR and VDBP genes appeared to be responsible for host susceptibility to human TB in a Taiwanese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 30 publications
1
21
1
1
Order By: Relevance
“…Epidemiological studies have revealed that VDR gene polymorphism is significantly associated with an increased risk of PTB in Venezuela, Iran, Turkey, and Han Taiwanese populations . Molecular epidemiological studies have also revealed that VDR polymorphism is significantly associated with an increased risk of PTB in tribal population of Chhattisgarh and southeastern region of India .…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have revealed that VDR gene polymorphism is significantly associated with an increased risk of PTB in Venezuela, Iran, Turkey, and Han Taiwanese populations . Molecular epidemiological studies have also revealed that VDR polymorphism is significantly associated with an increased risk of PTB in tribal population of Chhattisgarh and southeastern region of India .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, others studies described a significant association between VDR polymorphisms and risk to develop TB in Turkish (BsmI, p = .0006) (Ates et al., ), Gambian (TaqI, p = .01) (Bellamy et al., ), Chinese (FokI, p < .05) (Chen et al., ; Liu et al., ), Indian (Joshi et al., ) (BsmI, p < .002), Iranian (Banoei et al., ; Merza et al., ; Salimi, Farajian‐Mashhadi, Alavi‐Naini, Talebian, & Narooie‐Nejad, ) and Taiwanese (TaqI, p = .035; BsmI, p = .034) populations (Lee et al., ).…”
Section: Candidate Genes and The Risk Of Developing Tbmentioning
confidence: 93%
“…A recent study investigated four polymorphisms of restriction endonuclease sites for ApaI, TaqI, BsmI and FokI in VDR and of the three polymorphisms rs4588A/C/T (Thr420Lys), rs7041G/T (Asp416Glu) and rs4725C/T (Cys299Cys) in the vitamin D receptor binding protein ( VDBP ) in 198 TB patients and 170 healthy controls from a Han Taiwanese population. The TaqI, BsmI variants ( VDR ) and rs7041G/T (Asp416Glu) ( VDBP ) were significantly associated with susceptibility to TB . Although VDR polymorphisms were not associated with susceptibility to TB in an Iranian population, vitamin D deficiency was strongly related to TB susceptibility .…”
Section: Candidate Gene Studies In Tuberculosismentioning
confidence: 98%